Rol profesional posible, frente al lugar de la familia en un programa institucional del Estado - Olmos Zorrilla, Victoria Eugenia (Universidad de San Buenaventura - Cali, 2018)
This reflective article took place in an institutional setting that seeks to guarantee favorable conditions for the development of early childhood, through the incorporation of processes in the framework of initial education, care and nutrition to children under 5 years in the framework of comprehensive care; Having this context in mind, the situations that challenged me from my work as a psychologist, in the position of psychosocial professional, started from the feeling of having excessive demands from the professionals of the CDI, teachers, coordinator and nurse, in relation to the requirement of presence and accompaniment to families through constant summons to any eventuality that marked a problem with the child, situations that generated in me the sensation of disagreement in front of the representations of the situation, which led me to think or explore different ways of relating to families, in an attempt to claim another possible position in this institutional context, based on the question: what is it possible for parents to assume a position of authority if they are inscribed in an institutional artificiality that sanctions them? In this measure, the reflection started from understanding the place that the State assumes in front of the families and how these hegemonic discourses take place in the particular dynamics of the families and in the roles and practices assumed by the professionals of the CDI.